Reconstruction of a Neglected, Extensor Hallucis Longus Tendon Rupture Using Interposed Scar Tissue: A Case Report and Literature Review - Woo-Jong Kim (MDPI AG, 2021)
Injury of the extensor hallucis longus (EHL) tendon is relatively rare, but surgical repair is necessary to prevent deformity and gait disturbance. Primary suturing is possible if the condition is acute, but not when it is chronic. The scar tissue between the ruptured ends is a proliferative tissue composed of fibroblasts and collagen fibers. Given the histological similarity to normal tendons, several studies have reported tendon reconstruction using scar tissue. Here, we report a reconstruction of a neglected EHL rupture using interposed scar tissue. A 54-year-old female visited our clinic with a weak extension of a big toe. She had dropped a knife on her foot a month prior, but did not go to hospital. The wound had healed, but she noted dysfunctional extension of the toe and increasing pain. Magnetic resonance imaging (MRI) revealed that EHL continuity was lost and that the proximal tendon stump was displaced toward the midfoot. Scar tissue running in the direction of the original ligament was observed between the ruptured ends. In the surgical field, the scar tissue formed a shape similar to the extensor tendon. Therefore, we performed tendon reconstruction using the interposed scar tissue. For the first 2 postoperative weeks, the ankle and foot were immobilized to protect the repair. Six weeks after surgery, the patient commenced full weight-bearing. At the 3-month follow-up, active extension of the hallux was possible, with a full range of motion. The patient did not feel any discomfort during daily life. Postoperative MRI performed at 1 year revealed that the reconstructed EHL exhibited homogeneously low signal intensity, and was continuous. The AOFAS Hallux Metatarsophalangeal-Interphalangeal scale improved from 57 to 90 points and the FAAM scores improved from 74% to 95% (the Activities of Daily Living subscale) and from 64% to 94% (the Sports subscale). Scar tissue reconstruction is as effective as tendon autografting or allografting, eliminates the risk of donor site morbidity and infection, and requires only a small incision and a short operative time.